PENGARUH BELANJA TIDAK LANGSUNG DAN BELANJA LANGSUNG TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA TIMUR - Ignasia V. Dua Kuki; Munawar Munawar; Yosef Paseli Dheghu (P3M- Politeknik Negeri Kupang, 2019)
Economic growth means developments in the economy that causes the goods and services produced to increase and the prosperity of the people increase. An economy is in dire need of government participation in carrying out various types of spending. Indirect expenditure is a budget expenditure that is not directly related to the program or activity. Whereas direct expenditure is budget expenditure which directly related to the program or activity. In this study explains whether indirect expenditure and direct expenditure affect the economic growth in the province of East Nusa Tenggara. This research was conducted in five regencies/cities in NTT, which is Kupang, TTS, TTU, Belu Regency and Kupang City. The data used in this study is secondary data, the period 2013-2017 obtained from the Central Statistics Agency (BPS) of NTT Province. The variable used is an independent variable consisting of indirect expenditure and direct expenditure can affect the dependent variable, namely economic growth. The analysis model used is multiple linear regression with the SPSS 16.0 application program. The results of this study indicate that indirect and direct expenditure partially and simultaneously has no significant effect on economic growth in the province of East Nusa Tenggara. Then the rate of economic growth based on GRDP (Gross Regional Domestic Product) based on constant (real) prices over a period of five years (2013-2017) that occurred in five districts/cities in NTT Province has increased with a fairly good percentage of 5%.It can be concluded that government spending, namely indirect and direct expenditure, does not affect economic growth in NTT Province. If spending rises, economic growth will also increase. The regional government, especially the five Regencies/Cities in NTT Province, should optimize all their regional revenue potential so that the results can be used to increase the amount of allocation for regional expenditure. Efforts to improve the economy are also demonstrated by the development of economic sectors that are directly related to the wider community, such as agriculture, animal husbandry, trade, tourism, and industry.